Your Place or Mine? Does the Sleep Location Matter in Young Couples?. Issue 2 (4th March 2017) - Spiegelhalder, Kai; Regen, Wolfram; Siemon, Franziska; Kyle, Simon D.; Baglioni, Chiara; Feige, Bernd; Nissen, Christoph; Riemann, Dieter
Abstract : This study sought to characterize the impact of sleep location (own sleeping environment vs. partner's sleeping environment), social setting (sleeping in pairs vs. sleeping alone), and sex on sleep. An experimental 2 x 2 (sleep location x social setting) within-subject design was employed with 15 young heterosexual couples. The results suggest that sleep location does not appear to have a strong and consistent effect on sleep quantity or quality. The social setting had a specific effect in heterosexual young men, who were found to sleep longer and rise later when cosleeping with their partner. In contrast, we did not find any significant effect of the social setting on sleep continuity parameters in women. In both sexes, sleep quality was perceived to be better when sleeping in pairs. However, there was a higher concordance of the partners' body movements in cosleeping nights compared to the sleeping alone condition.